Utilization of fermented wheat bran extract medium as a potential low-cost culture medium for Chlorella ellipsoidea - Taslima, Akter; Md. Mahadi, Hasan; Mousumi, Das; Md. Nurunnabi, Mondal; Sahadat, Hossain; Mohammad Bodrul, Munir; Md. Amzad, Hossain (FSTS, UNIMAS, 2022)
Microalgae, Chlorella ellipsoidea is an excellent energy source for food and biofuel production. Nevertheless, the production cost of C. ellipsoidea using Bold's Basal Medium (BBM) is expensive, which led to exploring the alternation of a low-cost medium for large-scale production. Low-cost fermented wheat bran extract medium (FWBEM), which has good nutritional properties, might be an alternative approach to mass production of C. ellipsoidea. The present study was conducted to evaluate the growth and production of C. ellipsoidea using different concentrations of FWBEM. Wheat bran was fermented at the concentration of 8.33, 6.66, and 5.00 g/L water and used as treatments for T2, T3, and T4, respectively. The BBM was used as the control medium (T1). The growth and production of C. ellipsoidea were monitored at three days intervals through cell dry weight, specific growth rate, optical cell density, chlorophyll a content, and cell numbers. Those growth data revealed that C. ellipsoidea cultured at 6.66 g/L (T3) concentration did not vary significantly with the standard inorganic BBM. However, T2 and T4 showed substantially lower cell growth and chlorophyll a content than control and T3. Compared to the BBM, a significant reduction in production cost was obtained in the FWBEM. Based on the cell biomass growth, pigmentation, and production cost, FWBEM at a 6.66 g/L could be used as an alternative medium to BBM. Therefore, FWBEM has excellent potential to be used for the low-cost production of C. ellipsoidea.